Immigration and innovation - David C. Maré; Richard Fabling; Steven Stillman (Institute for the Study of Labor (IZA), 2011)
We combine firm-level innovation data with area-level Census data to examine the relationship between local workforce characteristics, especially the presence of immigrants and local skills, and the likelihood of innovation by firms. We examine a range of innovation outcomes, and test the relationship for selected subgroups of firms. We find a positive relationship between local workforce characteristics and average innovation outcomes in labour market areas, but this is accounted for by variation in firm characteristics such as firm size, industry, and research and development expenditure. Controlling for these influences, we find no systematic evidence of an independent link between local workforce characteristics and innovation.
urn:nbn:de:101:1-201105173225
Keywords: O31; R30; 330; innovation; immigration; local labour market